Outcome of Pelvic Fractures Identified in 75 Horses in a Referral Centre: A Retrospective Study - Moiroud, Claire H.; Coudry, Virginie; Denoix, Jean-Marie (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate the reliability of fracture location and horse sporting discipline as prognostic indicators after a pelvic fracture in a referral centre caseload.Materials and Methods Data were collected for the short- and long-term follow-up of all cases with a diagnosis of pelvic fracture in a 7-year period. Information was obtained for 75 horses through a postal and internet survey. The proportion of horses returning to competition following fractures was compared between groups according to the competition discipline and the characteristics of the fracture.Results Forty-six of 75 horses returned to or began their intended activity. This proportion was significantly lower in the group of horses that sustained a comminuted fracture irrespective of the fracture location (11/25, p = 0.05). The proportion of Standardbred trotter racehorses returning to a sporting career after pelvic fracture (9/20) was not significantly different from horses competing in other disciplines (37/55). Cases of multiple pelvic fractures in the study population, and particularly those involving the acetabulum, had the worst sports prognosis (2/8 and 0/4). Nevertheless, two foals and one yearling (3/5) with isolated fracture of the acetabulum went on to race.Clinical Significance A clear characterization of the fracture is essential for prognosis, as comminuted fractures seem to entail a poorer athletic prognosis. Despite a lack of significance, prognosis seems poorer for Standardbred trotter racehorses and for cases with acetabulum involvement in multiple fractures. These results should be confirmed in larger samples.
Keywords: pelvis; fracture; athletic prognosis; racehorses; sporthorses